‘Show us your moves’: trade rituals of television marketing - Grainge, Paul; Johnson, Catherine (Emerald, 2015)
The purpose of this paper is to examine the professional culture of television marketing in the UK, the sector of arts marketing responsible for the vast majority of programme trailers and channel promos seen on British television screens. In research approach, it draws on participant observation at Promax UK, the main trade conference and award ceremony of the television marketing community. Developing John Caldwell’s analysis of the cultural practices of worker groups, it uses Promax as site of study itself, exploring how a key trade gathering forges, legitimates and ritualizes the identity and practice of those involved in television marketing. Its findings show how Promax transmits industrial lore, not only about ‘how to do’ the job of television marketing but also ‘how to be’ in the professional field. If trade gatherings enable professional communities to express their own values to themselves, Promax members are constructed as ‘TV people’ rather than just ‘marketing people’; the creative work of television marketing is seen as akin to the creative work of television production, and positioned as part of the television industry. The value of the paper is the exploration of television marketing as a professional and creative discipline. This is especially relevant to marketing and media academics who have tended to overlook, or dismiss, the sector and skills of television promotion.